50 Clinical outcomes following bailout stenting in patients treated with paclitaxel coated balloon versus sirolimus coated balloon; synergy or toxicity?. (17th July 2020) - Liu, Boyang; Khattak, Sophia; Ishaq, Mohammed; Athukorala, Sampath; Watkin, Richard; Lee, Kaeng; Pulikal, George; Ment, Jerome; Bhatia, Gurbir; Freestone, Bethan; Pitt, Michael; Vigano, Elena
Abstract : Aims: The bailout stenting post-drug coated balloon (DCB) is performed with second generation drug eluting stents (DES). For paclitaxel DCBs (PCB), it will result in delivery of 2 different drugs to the vessel wall (Paclitaxel from DCB + Limus from DES), on the contrary for sirolimus DCBs (SCB) it will result in double dose of a same drug (Limus from DCB + Limus from DES). In this study, we study the differences in the clinical outcomes between the two groups (PCB + Limus stent vs. SCB + Limus stent) assessing for either a synergistic or a toxic-effects. Methods and Results: We evaluated patients treated with DCB between January 2016 and June 2019 at our centre. Results are reported as death, cardiac death, target vessel myocardial infarction (TVMI), target lesion revascularisation (TLR) and MACE (combination of cardiac death, TVMI and TLR). During the study period; 890 lesions (766-patients) were treated with DCB. Of them; 433 were treated with PCB and 477 with SCB. Total of 81-lesions (9%) needed bailout stenting for either dissection and/or recoil of >50%. This included; 42-lesions in PCB group and 39-lesions in SCB group. There were no significant differences in the baseline characteristics between the two groups. During the median follow-up period of 18-months, the clinical outcomes between PCB and SCB group were; death: 3 (7%) vs. 0; p=0.3, cardiac death: 2 (5%) vs. 0; p=0.5, TVMI: 0 vs. 1 (2.6%); p=0.4, TLR: 1 (2.4%) vs. 3 (7.7%); p=0.5, MACE: 3 (7%) vs. 3 (7.7%); p=0.7. There were no reported cases of stent thrombosis in either group. Conclusions: The bailout stenting rate was relatively low in our group (9%) as compared to previously published studies. No significant differences were observed between the two-bailout stenting groups, although numerically PCB + limus stent group had lower rates of TLR, but had higher mortality rates as compared to SCB + limus stent, implying potential synergistic effect, but maybe at the cost of toxicity? This needs to be confirmed with larger patient group with multi-centre experience. Conflict of Interest: None